2021
DOI: 10.1088/1361-6579/abcb5c
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance phase angle in elite male athletes: a segmental approach

Abstract: Objective: Phase angle (PA), a bioelectrical impedance analysis (BIA) parameter, has proven to be a proxy of body cell mass in athletes, but very few data are available on its segmental evaluation (upper and lower limbs). Therefore, we aimed to assess whether whole-body and segmental PA varied among elite male athletes of different sports and compared these to control groups. Additionally, we investigated its relationship with anthropometric and body composition parameters. Approach: Elite athletes practicing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…However, as shown by Silva et al (31), there is a lack of agreement between the bioimpedance parameters measured with different devices. Therefore, the BIA-data presented in this study may not be comparable with those of Marra et al (30) where R and Xc were obtained using a multifrequency device. Our athletes were plotted on reference ellipses created starting from measurements made with the same frequency and method of measurement.…”
Section: Role Of the Upper Limbs In Rowerscontrasting
confidence: 83%
“…However, as shown by Silva et al (31), there is a lack of agreement between the bioimpedance parameters measured with different devices. Therefore, the BIA-data presented in this study may not be comparable with those of Marra et al (30) where R and Xc were obtained using a multifrequency device. Our athletes were plotted on reference ellipses created starting from measurements made with the same frequency and method of measurement.…”
Section: Role Of the Upper Limbs In Rowerscontrasting
confidence: 83%
“…In constitutionally lean people and ballet dancers, despite lower BMI, phase angle is not decreased. The explanation of this fact is body composition—less fat and more muscle mass as a result of workout [ 43 , 59 ]. For ski jumpers who practice lower BMI simultaneously with a lower percentage of body fat, the same tendency may be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Among trained athletes, this value rises and may reach the 8.5° [ 18 , 39 ] to 9.5° [ 40 ] range. A large variability in the whole-body PhA values is observed for the same sport and between various sports [ 41 , 42 ], but the availability of data concerning the assessment of segmental PhA is still limited [ 43 ]. Segmental (five compartments: trunk, lower and upper limbs) evaluation could be useful for monitoring the condition of the athlete preparing for a competition and for assessing differences among athletes [ 15 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…more body cell mass relative to FFM), cellular integrity and cell functions [28]. It may represent a proxy parameter of muscle quality in athletes, being signi cantly associated with physical activity and muscle strength [29,30]. A recent systematic review showed that PhA was higher in athletes vs controls whereas it was still uncertain to what extent PhA differs among various sports [31].…”
Section: Discussionmentioning
confidence: 99%